2021
DOI: 10.1002/pol.20210115
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized acrylic polyhydroxy urethanes as molecular tool box for photocurable thermosets and 3D printing

Abstract: Liquid urethane (meth)acrylates represent attractive components of photocurable thermosets for applications ranging from coatings and adhesives to 3D printing. Herein we tailor liquid polyfunctional urethane methacrylates (UMA) derived from acrylic polyhydroxy urethanes. Cyclic carbonate methacrylates react with diamines to form dihydroxy-functional urethane dimethacrylates. In an "onepot" process the hydroxy groups are functionalized either by reaction with 2-isocyanatoethyl methacrylate (IEMA) or by esterifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Despite HU-CL 5 -A being an acrylate, it could not be cured as the sole monomer because of its relatively high viscosity and restricted chain mobility. Hence, mixing it with ACMO as a reactive diluent at a proportion of 40/60 (wt/wt) was successful in getting a cured film, similar to previous studies, 10,11 whose swelling index (SI) and gel content (GC) in THF were found to be 79.7% ± 1.3 and 87.4% ± 1.2, respectively. Since ACMO and HU-CL 5 -A dissolve in THF, the high GC F I G U R E 1 Conversion of CL tracked from 1 H-NMR using signals of two different proton sets (the disappearance and appearance of protons at 4.23 and 3.65/4.07 ppm (method 1), respectively, and those of 2.64 and 2.33 ppm (method 2), respectively).…”
Section: Photocurable Thermosets and Degradation Studysupporting
confidence: 84%
See 4 more Smart Citations
“…Despite HU-CL 5 -A being an acrylate, it could not be cured as the sole monomer because of its relatively high viscosity and restricted chain mobility. Hence, mixing it with ACMO as a reactive diluent at a proportion of 40/60 (wt/wt) was successful in getting a cured film, similar to previous studies, 10,11 whose swelling index (SI) and gel content (GC) in THF were found to be 79.7% ± 1.3 and 87.4% ± 1.2, respectively. Since ACMO and HU-CL 5 -A dissolve in THF, the high GC F I G U R E 1 Conversion of CL tracked from 1 H-NMR using signals of two different proton sets (the disappearance and appearance of protons at 4.23 and 3.65/4.07 ppm (method 1), respectively, and those of 2.64 and 2.33 ppm (method 2), respectively).…”
Section: Photocurable Thermosets and Degradation Studysupporting
confidence: 84%
“…The resulting HU-CL 5 is acrylated with acryloyl chloride (ACl) to finally obtain the photocurable macromonomer diacrylate, HU-CL 5 -A. However, the photocuring was achieved by diluting the diacrylates with ACMO, similar to Mülhaupt et al's studies, 10,11 to prepare the final degradable films which can be used not only as coatings and materials for 3Dprinting, like previously reported, but also as patches and films for biomedical applications. The following study is divided into two main parts: a synthesis section focusing mainly on the ring-opening polymerization (ROP) of CL followed by the examination of the final film after degradation and identifying the degradation products.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations